Enhancing yield, water productivity, energy efficiency and economic returns of wheat by optimizing irrigation and nitrogen management practices - MANDAL, ABHIJIT; SINGH, TEEKAM; SARKAR, AYAN; DASS, ANCHAL; CHAUDHARY, MANOJ; PADHAN, SMRUTI RANJAN; KAUR, RAMANJIT (Journal of Soil and Water Conservation, 2025)
India’s agricultural landscape faces critical challenges in water and nitrogen management, prompting a study to optimize irrigation techniques and enhance sustainability in wheat production. Five irrigations produced the highest grain yield closely followed by three irrigations but 29% more than 2-irrigations due to moisture and heat stress during the grain filling stage. Nitrogen management also significantly impacted yield, with 100% recommended dose of nitrogen (RDN) yielding the highest at 4.32 t/ha, 7% more than the second-best treatment which combined 50% RDN with two nano-urea sprays. The highest water productivity was achieved with three irrigations recording 1.56 kg/m³, which was 41.82% more compared to two irrigations (1.17 kg/m³) due to higher yield with slightly higher water consumption. The 100% RDN also resulted higher water productivity (1.50 kg/m3) surpassing control plot by 275%. Five times irrigations maintaining higher soil moisture levels compared to others, particularly during the harvest stage. The net return after raising the crop was higher with 3-irrigations which was highest (55990 Rs/ha) and net return of 82130 Rs/ha was obtained from 100% RDN which was superior over rest of the N levels. Energy analysis revealed that while five irrigation and 100% RDN required the highest energy inputs but 50%RDN+ 2 nano urea spray demonstrated superior energy efficiency. Three irrigations with 100% RDN treatment were identified as the most effective practices for optimizing yield, water productivity, and economic returns in wheat cultivation.